The activities of factory «Prowodnik» in Riga and its employees – graduates of the Riga Polytechnicum / Riga Polytechnic Institute - Zigmunde, Alīda; Šapovalovs, Oļegs (History of Engineering Sciences and Institutions of Higher Education, 2018)
The article gives an overview of the activities of rubber, gutta-percha and telegraph factory «Prowodnik» in Riga, founded in 1888. Before the First World War, the factory was one of the four largest rubber factories in the world. During the First World War, in 1915, the factory was evacuated to Moscow, in 1918, it was expropriated.  In 1921, the shareholders decided to re-establish «Prowodnik» in its old premises in Riga, but the economic situation had changed. For some years it operated as a woodworking factory (1925–1935), but it never reached the boom it had experienced at the end of the 19th century and at the beginning of the 20th century. At the end of the 1930s the factory was liquidated. The alumni of the Riga Polytechnicum (RP) and Riga Polytechnic Institute (RPI) who had given significant input in its achievements have been identified by the authors of this article.